'My story is like a magic wand': a qualitative study of personal storytelling and activism to stop violence against women in Turkey. Issue 1 (1st January 2021) - Mwaba, Kasonde; Senyurek, Gamze; Ulman, Yeşim Işıl; Minckas, Nicole; Hughes, Peter; Paphitis, Sharli; Andrabi, Shazana; Ben Salem, Lobna; Ahmad, Lida; Ahmad, Ayesha; Mannell, Jenevieve
ABSTRACT: Background : Telling personal stories of violence has been central to recent advocacy efforts to prevent violence against women around the world. In this paper, we explore the use of personal storytelling as a form of activism to prevent femicide in Turkey. This study is part of a broader storytelling initiative called SHAER (Storytelling for Health: Acknowledgement, Expression and Recovery) to alleviate the psychological and emotional suffering of women who have experienced gender-based violence in high-prevalence settings. Objectives : We conceptually explore personal stories of violence as a form of both distributed agency and activism. This conceptual framework is used to answer the following research question in the Turkish context: How do women use their personal stories of interpersonal violence for their own benefit (support) and that of others (activism)? Methods : Our study is based on 20 in-depth semi-structured interviews with women who have experienced violence and were purposefully recruited by the 'We Will End Femicide' Platform in Istanbul. Interviews were conducted between March and August 2019. We used inductive and deductive thematic analysis to identify instances of personal storytelling at three levels: intrapersonal, relational and collective. Results : Our results show how the use of personal storytelling can provide a means of healing from experiences of violence. However, this process is not linear and is often influenced by the surrounding context including: the listener of the story, their reaction, and what social networks the woman has to support her. In supportive social contexts, personal storytelling can be an effective support for activism against violence: personal stories can provide opportunities for individuals to shape broader discourses about violence against women and the right of women to share their stories. Conclusions : Telling one's personal story of violence can both support women's agency and contribute to the collective struggle against violence against women more broadly.